Efforts By Islamic Religious Education Teachers To Address Feudal Perceptions In Teacher-Student Relationships At Al-Qur’aniyyah Islamic High School - Muhammad Akyas Nabil; Jamil Abdul Aziz (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study examines the efforts of Islamic Religious Education (PAI) teachers in addressing misperceptions of feudalism at SMA IT Al-Qur'aniyyah. The research was motivated by the tendency of some students to perceive teachers as unquestionable authority figures and to interpret respect as absolute obedience, which may hinder active participation in the learning process. The purpose of this study was to identify the forms and causes of feudalistic misperceptions and to analyze the strategies employed by PAI teachers to overcome them. This study used a qualitative descriptive approach and was conducted at SMA IT Al-Qur'aniyyah. Data were collected through interviews, observations, and documentation, with PAI teachers serving as the main informants. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings revealed that feudalistic misperceptions were influenced by students’ internal factors, family environment, school culture, and inaccurate understanding of Islamic manners (adab). PAI teachers addressed these issues through classroom instruction, character building, dialogical learning, and exemplary behavior. These efforts contributed to positive changes in students’ attitudes, including greater confidence, active participation, and a better understanding of equality and mutual respect in Islam.